Answer:
The standard form would be 5x + 6y = 8
Step-by-step explanation:
To find the equation between these two points, start by finding the slope. You can do this using the slope formula.
m(slope) = (y2 - y1)/(x2 - x1)
m = (3 - -2)/(-2 - 4)
m = 5/-6
m = -5/6
Now that we have the slope, we can use that and a point in point-slope form. Once we have that we can solve for the constant and rationalize the denominator for the standard form.
y - y1 = m(x - x1)
y - 3 = -5/6(x + 2)
y - 3 = -5/6x - 5/3
5/6x + y - 3 = -5/3
5/6x + y = 4/3
5x + 6y = 8